Differential Effects of Albumin Infusion between ICU and Non-ICU Hypoalbuminemia Patients - Mariana, Nina; Wijaya, Surya Oto; Setyawati, Rumaisah; Maemun, Siti; Nafrialdi, Nafrialdi (Pharmaceutical Journal of Indonesia, 2021)
Background: Hypoalbuminemia is frequent among hospitalized patients and is associated with poor outcomes. ICU patients are widely associated with more severe condition making albumin correction seems to be less effective. This study was aimed to compare the results of albumin correction in ICU and non-ICU patients at Sulianti Saroso Hospital, Jakarta. Methods: A cross sectional study was conducted on adult patients in ICU and non-ICU wards who received intravenous albumin infusion at Sulianti Saroso hospital, between January 2013 to March 2018. Paired t-test was used to analyze the changes of albumin level before and after albumin infusion. Results: 123 ICU patients (41 sepsis, 82 non-sepsis) and 206 non-ICU patients (34 sepsis, 172 non-sepsis) who received 20% or 25% albumin infusions were included. Significant increase in albumin levels were observed in sepsis patients both in ICU and non-ICU, while in non-sepsis patients, the significant increase only observed in non-sepsis patients. Overall, mean increase in albumin levels in ICU-and non-ICU patients were 0.13 (0.63) g/dL vs 0.35(0.54) g/dL, respectively (P= < 0,001). Conclusion: Non-ICU patients show better response to albumin infusion compared to ICU patients. This difference is presumably due to different degree of inflammation. It is suggested that the quantity needed for albumin infusion is calculated differently according to clinical condition of the patients